Uploading selves: Inuit digital storytelling on YouTube - Wachowich, Nancy; Scobie, Willow (Études/Inuit/Studies, 2010)
This article explores the contemporary use of open-access video-sharing sites by Inuit youth and young adults. Based on 12 months of cyber-fieldwork and focused specifically on YouTube, it explores how Inuit young people across the Canadian Arctic are using online spaces to post short excerpts from their lives and connect with others. The paper situates these digital autobiographies in the recent trajectory of Inuit storytelling, showing that Internet technology allows individual narrators the freedom to bypass established rules and institutions of cultural representation. Self-produced videos posted online are more multivalent, dialogical, and provocative expressions of Inuit selfhood than those texts that may have circulated in the past. While the Internet has been celebrated for its global reach, many of the social relationships and dialogues seemingly fostered by this technology are intimate and localised. Inuit youth and young adults use video-sharing technology to creatively mediate pasts, presents, and futures in the creation of new social worlds.